Four highland species of Galianthe (Rubiaceae: Spermacoceae) with restricted distribution in South America: conservation assessment and complete descriptions - Florentín, Javier E.; Nuñez Florentin, Mariela; Barea Pastore, José Floriano (Phytotaxa, 2019)
Full descriptions of four Galianthe species, complemented by new data on fruits and seed characters are presented. These species occur at 500–3000 m elevations: G. gertii and G. reitzii in southeastern Brazil; G. guaranitica in eastern Paraguay and central-western Brazil; and G. boliviana in the sub-Andean region of northern Bolivia and southern Peru. Conservation status, with comments on distribution, is provided for three of them and is reassessed for one. The lectotypification of G. guaranitica is discussed.